Eco-friendly Corrosion Inhibitor Coatings Based on Plant Waste Extracts: A Comparative Study of Tea Waste and Orange Peel - Filardli, Abdullah Malik Islam; Fadilah, Muhammad Zidan; Syahrizal, Muhammad Isyar; Rahmawati, Mafniatul; Febriani, Anisa Dwi; Adhilisty, Clarissa Mayla; Pratiwi, Latifah Indah; Salsabila, Ulfa Mazroatus; Setiawan, Naufal Dafa Akbar; Syahputra, Muhammad Rakha; Ghani, Afzaal Zaydan (Jurnal Sains dan Aplikasi Keilmuan Teknik Industri (SAKTI), 2025)
This study seeks to assess the efficacy of plant-based waste extracts, namely orange peel extract and tea waste extract, as natural corrosion inhibitors for mild steel submerged in a 3.5% NaCl solution. The methodology adhered to ASTM G31 standards, employing mild steel specimens coated with each extract using three application techniques: brushing, immersion, and spraying. The weight loss method was used to measure corrosion rates (Mmpy), enabling the calculation of inhibition efficiency (IE%) for each specimen. The uncoated control specimen consistently exhibited the highest corrosion rate (3.4523 Mmpy), categorized as "Poor." Specimens treated with orange peel extract showed significantly lower corrosion rates, with the brushing method yielding an inhibition efficiency of 98.7%, categorized as "Excellent." Likewise, specimens coated with tea waste extract demonstrated remarkable inhibition, with the brushing and immersion techniques achieving efficiencies of 98.9% and 97.7%, respectively. These results indicate that both orange peel and tea waste extracts serve as promising, eco-friendly alternatives for corrosion protection of mild steel, with their effectiveness significantly influenced by the method of application.